2005
DOI: 10.18060/74
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Global Social Work

Abstract: This article addresses the social work within the context of internationalism and globalization. Based on an examination of published documents on international social work in the past decade, the authors make an evidence-based projection of what is likely to occur in the future of global social work. Finally, the authors make a social work values-based projection of what should occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The 10-year period from 1995 to 2004 provided a time span sufficient to observe changes in two blocks of time: 1995-9 and 2000-4. The 1995-2004 time period is also consistent with the time period employed in a previous article on globalization by Potocky- Tripodi and Tripodi (2005). All of the articles (N=2321) in the seven journals over a 10-year period were analyzed and classified as research or non-research.…”
Section: Methodsmentioning
confidence: 71%
See 2 more Smart Citations
“…The 10-year period from 1995 to 2004 provided a time span sufficient to observe changes in two blocks of time: 1995-9 and 2000-4. The 1995-2004 time period is also consistent with the time period employed in a previous article on globalization by Potocky- Tripodi and Tripodi (2005). All of the articles (N=2321) in the seven journals over a 10-year period were analyzed and classified as research or non-research.…”
Section: Methodsmentioning
confidence: 71%
“…In addition, Hokenstad and Midgley (2004) demonstrated that international social work research can help countries to learn about and possibly adopt successful social policies and programs that have been implemented in other countries. Indeed, in a content analysis of article abstracts retrieved from the Social Work Abstract database for 1995-2004, using the term 'international social work', it was found that 57 percent of the articles (n ¼ 279) employed social research methods (Potocky- Tripodi and Tripodi, 2005). However, clear distinctions of different types of international social work research were not evident, and the degree to which comparative research has increased or decreased over time could not be ascertained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation